Justice from below: corporate accountability in Argentina - Pereira, G; Payne, LA; Bermúdez, LB (Taylor and Francis, 2022)
Argentina has taken a protagonist role in corporate accountability for crimes against humanity committed during the past authoritarian regime (1976-1983). This study examines in-depth the factors that allowed for those advances. It highlights the role of victims, human rights groups, and their advocates in demanding justice for gross human rights violations perpetrated by an alliance of economic and state actorsinvolved in them. It considers the role institutional innovators within the judicial realm advanced these demands, translating them into legal actions. This combination of forces ‘from below’ has made Argentina a leader in corporate accountability, capable of overcoming barriers posed by a powerful veto by the business sector. Not all processes advance victims’ rights, however. Using an original database of cases, the article develops an accountability scale to develop Archimedes’ lever approach to explain movement along it. Specifically, in the right context and with the right tools, even relatively weak victims in the Global South can lift the weight of corporate accountability. The article concludes by highlighting the tools that are transferable to other country contexts.